Optimization of a Cesium-Sputter Ion Source for Use in Accelerator Mass Spectrometry - Tiessen, Collin (Université d'Ottawa / University of Ottawa, 2022)
Accelerator Mass Spectrometry (AMS) is a sensitive technique for the analysis of rare isotopes. Optimizing the output of the cesium-sputter ion source is a fundamental method for improving measurement precision, efficiency, and reliability. Several strategies for improving the ion source are discussed and lead to an understanding of the electrodynamics within the ion source to inform further improvement in design and operating parameters. At the Andr´e E. Lalonde Accelerator Mass Spectrometry Laboratory (Lalonde AMS), the High Voltage Engineering Europa (HVEE) SO-110C ion source was modelled using Integrated Engineering Software (IES)’s Lorentz-2E ion trajectory simulation software. Lorentz-2E incorporates the mutual space-charge interaction between the positively charged cesium ion beam and the sputtered negative ion beam. A critical component of this work was the development of the Rijke code. Rijke communicates with Lorentz-2E to initiate, generate, and run varied sequences of simulations, as well as analyze and record the input and output data in formats convenient for timely analysis. This software and its interconnection with Lorentz- 2E is described in extensive detail for a prospective user. Initial simulation work examined the effects of modifying various electrode geometries within the source such as the extraction cone, the target aperture, a simple cratered sample model as well as examining the effects of varying the cesium ion current. The self-repulsion of cesium was found to be important at currents of 250 µA and above. At high enough cesium currents, the expansion of the cesium beam is such that parts of it impinge outside the extents of the sample material. Through both simulation and experiment, it was demonstrated that this effect can be mitigated by either recessing (translating along the axis of symmetry away from the ionizer) the target holding the sample or by adjusting the potential difference between the target and ionizer. Experimentally, at routine settings (6 kV target to ionizer potential, 115 ◦C cesium oven temperature, and 35 keV output energy), a target recess of 1 mm gave the most stable and sustained output of 12C from graphite blanks. While the peak current was less than the unrecessed case, the total measured charge from the recessed target was higher. Cesium currents at these routine settings were found to be below the theoretical space-charge limited maximum. Using 10Be standards, a multi-dimensional experimental study examined the effects of increasing the cesium current, adjusting the target-ionizer potential from 4 to 11 kV, while also examining target recesses of 0 to 4 mm. Multiple combinations of these settings produced enhanced currents of 9Be2+, measured at the high-energy offset Faraday cup, as high as 13.5 µA. This was higher than previously observed, resulting in the most precise measurement of 10Be performed to date at Lalonde AMS. The electrodynamics within the ion source can be characterized as three competing processes: a) a strong locus of positive space charge located at the centre of the sample, depending primarily on the focusing of the cesium beam, which draws negative ions across the axis of symmetry; b) a bulk positive space charge external to the negative ion beam, depending primarily on the magnitude of the cesium current, draws the outer-most negative ions away from the axis; and c) the raw field from the electrode potentials and geometry which is mainly defocusing for negative ions. These effects are mitigated the most when the cesium beam is distributed across the entire sample surface with the additional critical benefit of maximizing the sample material accessed for sputtering. This thesis work has demonstrated that both the mutual and self space-charge interaction of the cesium and negative ion beams were critically important and that the use of the simulation software can inform both improved design and operation settings of the ion source.
Keywords: Carbon-14; Accelerator mass spectrometry; Ion optics; Simulations; Ion sources